HUBUNGAN PENGETAHUAN DAN PARTISIPASI IBU DI POSYANDU DENGAN STATUS GIZI BALITA - Winda Surita; Zulfiana Dewi; Rahmani Rahmani; Magdalena Magdalena (JOURNAL HEALTH AND NUTRITIONS, 2026)
Stunting remains a significant problem in the Tandilang Community Health Center area, with a prevalence of 23% in 2024. Although community participation in Posyandu activities has increased, geographical barriers and limited food access are suspected to affect the nutritional status of children. The study aimed to analyze the relationship between maternal knowledge and participation in Posyandu with the nutritional status of children aged 12-59 months. The study used an analytical observational design with a cross-sectional approach. The population was all children under five in the working area, with a subject of 118 children selected by purposive sampling. Data were collected from September to November 2025 through questionnaire interviews and anthropometric measurements. Data analysis used the Chi-Square test. The result of study revealed that the majority of mothers had good knowledge (83.90%) and actively participated in Posyandu (82.20%). However, the proportion of stunted (40.68%) and severely stunted (6.78%) children was high. Bivariate analysis showed no significant relationship between maternal knowledge (p=0.919), Posyandu participation (p=0.769) and the nutritional status of children. The conclusion was showed that high maternal knowledge and active participation do not guarantee optimal nutritional status in children, indicating a knowledge-practice gap influenced by external factors such as economic and environmental conditions. It is recommended that health centers develop comprehensive nutrition programs, including sanitation improvement and integration of infectious disease management.Stunting masih menjadi masalah di wilayah kerja Puskesmas Tandilang dengan prevalensi 23% pada tahun 2024. Meskipun partisipasi masyarakat dalam Posyandu meningkat, hambatan geografis dan akses pangan diduga memengaruhi status gizi balita. Penelitian ini bertujuan menganalisis hubungan pengetahuan dan partisipasi ibu di Posyandu dengan status gizi balita usia 12-59 bulan. Penelitian menggunakan desain observasional analitik dengan pendekatan cross-sectional. Populasi adalah seluruh balita di wilayah kerja, dengan subjek sebanyak 118 balita yang dipilih secara purposive sampling. Pengumpulan data dilakukan pada bulan September-November 2025 melalui wawancara kuesioner dan pengukuran antropometri. Analisis data menggunakan uji chi-square. Hasil penelitian menunjukkan bahwa mayoritas ibu memiliki pengetahuan baik (83,90%) dan berpartisipasi aktif di Posyandu (82,20%). Namun, proporsi balita pendek (40,68%) dan sangat pendek (6,78%) masih tinggi. Analisis bivariat menunjukkan tidak ada hubungan signifikan antara pengetahuan ibu (p=0,919) dan partisipasi Posyandu (p=0,769) dengan status gizi balita. Kesimpulan penelitian menunjukkan bahwa tingginya pengetahuan dan partisipasi aktif ibu belum menjamin status gizi balita optimal, mengindikasikan kesenjangan pengetahuan-praktik yang dipengaruhi faktor eksternal seperti kondisi ekonomi dan lingkungan. Disarankan Puskesmas mengembangkan program gizi komprehensif, termasuk perbaikan sanitasi dan integrasi penanganan penyakit infeksi.